Complete the process of solving the equation.

Fill in the missing term on each line. Simplify any fractions.
2(c + 6) = 12

c + 6 =

1 answer

Divide both sides of the equation by 2.

(c + 6)/2 = 12/2

Simplify.

c + 6 = 6
Similar Questions
  1. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. 2(u+5)=10 u+5=
    1. answers icon 1 answer
  2. orComplete the process of solving the equation. Fill in the missing term on each line. Simplify any fractions. – 2(15r–12)=
    1. answers icon 1 answer
  3. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. c/ –5–10=5 c/
    1. answers icon 1 answer
  4. Complete the process of solving the equation.Fill in the missing term on each line. Simplify any fractions. 20(c–11)= –20
    1. answers icon 1 answer
more similar questions